Skeletal Maturation in the pediatric population in a large tertiary care hospital in South India - G, Vijayalaksmi; Rajiah, Jeya (International Journal of Medical Research and Review, 2016)
Background & Objectives: Determination of skeletal age is an important part of examination for many clinical problems with growth disorders. The Greulich and Pyle atlas method and the Tanner Whitehouse technique are used to assess bone age accurately. However time constraints force pediatricians to quickly assess bone age from age of appearance of epiphyseal centres. The aim of this study was to re-examine this method in today’s clinical practice to enable more practical and appropriate use. Methods: The study was undertaken in The Institute of Child Health and Hospital for Children, Egmore,(ICH & HC) Chennai. Normal children less than 12 years were included in the study. The children were grouped in different age groups, 100 girls and 100 boys in each age group totalling 3800 children. Depending on the chronological age of the child only the x ray films of the hand, wrist, elbow, or knees were taken. We used x-rays of hands for all age groups and elbow in those over 5 years. Only the appearance of ossification centers was noted. We also used x-ray of the patella for children in 3 to 5 year age groups. Results: We found that the mean age of appearance of patellar ossification was similar in both boys and girls (mean age 4.8± 0.5). By 3-6 months capitate and hamate were present in all children (mean age 0.5± 0.1). There is high variability in the timing of ossification of carpal bones, which accounts for their elimination for age evaluation. However the pisiform follows a constant mean age at 10.6 for girls and 11.6 for boys. Conclusion: Children can be adequately screened for age assessment from x rays of the hands in the early stages (upto 2 and half years) and later the elbows. We propose the use of knees lateral for patellar centre for children more than 3 and less than 6.